Gender, Generational Status, and Parent–Adolescent Sexual Communication: Implications for Latino/a Adolescent Sexual Behavior. (9th January 2015) - Deutsch, Arielle R.; Crockett, Lisa J.
Abstract : There is little research on how specific parent–adolescent sexual communication topics influence Latino/a youth's sexual behaviors, and how gender and generational status may moderate effects. This study examined effects of three different messages on intercourse and condom use among 1, 944 Latino/as from the National Longitudinal Study of Adolescent Health (T1 mean age = 15.46; SD  = 1.50). Results indicated discussing health consequences predicted higher odds of intercourse 1 year later across gender and generation groups. Birth control recommendation effects on subsequent intercourse and condom use differed by generational status and gender. Results indicated that message content is important for understanding effects of parent–adolescent sex communication on adolescents' behavior and underscored the need to consider gender and generational status in Latino/a parent–adolescent sexual communication studies.